Participatory natural resources management through multiple interventions at Galessa and the surrounding areas, central Ethiopia - Mekonnen, Kindu; Adimassu, Zenebe; Gorfu, B. (International Livestock Research Institute, 2011)
The paper discusses the different Natural Resources Management (NRM) approaches and interventions employed to reduce soil erosion and fertility depletion, and increase land productivity. It also emphasizes empirical research interventions, lessons and challenges.